Cost-Volume-Profit Analysis as a Tool for Financial Resilience Amid Macroeconomic Volatility: Empirical Evidence from PT Wilmar Cahaya Indonesia Tbk - Moh Adistian; Neng Dinda Septia; Muhammad Fauzan Akbar Rafsanjani; Neysha Putri Vaquitasari; Asri Sundari (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the Break-Even Point (BEP) and Margin of Safety (MOS) as Cost-Volume-Profit (CVP) indicators for evaluating sales safety and profit planning at PT Wilmar Cahaya Indonesia Tbk (CEKA) during 2022–2024. Research Method: A descriptive quantitative case study was employed using audited annual financial statements as secondary data obtained from the Indonesia Stock Exchange. Cost accounts were classified into fixed and variable costs using the Account Analysis Method based on the Notes to Financial Statements (CALK). Data were analyzed using Cost-Volume-Profit (CVP) through the calculation of the Contribution Margin Ratio, Break-Even Point, and Margin of Safety. Results and Discussion: Net sales increased from IDR 6.14 trillion in 2022 to IDR 8.00 trillion in 2024. The Margin of Safety Ratio rose from 60.37% to 70.19%, while the Break-Even Point remained relatively stable, indicating an increasing sales safety margin. Inflation, exchange rates, and crude palm oil (CPO) prices were used only as contextual information in interpreting the findings. Implications: The findings support managerial decision-making in sales safety evaluation, cost control, and profit planning through periodic CVP analysis. Originality: This study positions Margin of Safety as a sales safety indicator within the CVP framework and interprets macroeconomic conditions as contextual information rather than causal determinants.